Hubungan Pengetahuan Dan Motivasi Kader Posyandu Dengan Kepatuhan Pengisian Kms Balita Di Desa Pucangan Dan Kelurahan Kartasura - Putri, Zulaicha Hartono, Purwanti, SKM., M.Kes (2016)
Inwrought service post cadre is also claimed to have the knowledge which enough about duty and its responsibility, like way of balance, admission filling of KMS and giving side dish. ambulatory inwrought service post management also better if all cadre have the high motivation. Record-Keeping KMS completely represent one of important indicator in service of balita nutrition, because to watch the history growth the child, as well as a means of early detection to risk of obesity and malnutrition. Affect if cadre do not know the mechanism of record-keeping KMS of hence difficulty will to determine growth status and child growth. Purpose of this research is to know the correlation of between inwrought service post cadre knowledge and motivation with compliance of admission filling under five years KMS in Pucangan Village and Kartasura Sub-District. This research type was analytic observational analysis with cross sectional approach by sampel counted 39 cadre consisted of 19 cadre in Pucangan Village and 20 cadre in Kartasura Suib-Distric and was taken by total sampling. The data analyse technique use chi square test. Result of analysis known the majority of cadre age 27-36 years old (46,15%), have an education Senior High School/on an equal (64,1%), working as housewife (48,72%), have a cadre during >10 year (56,41%), have got construction (79,49%) and have got training (87,18%). From 39 cadre majority have middle knowledge (56,4%), have midlle motivation (48,7%) and obey in filling under five year KMS (64,1%). Research result shows that there was correlation cadre knowledge with faithfullness of compliance fill KMS (p-value 0,000< 0,05) and there was correlation cadre motivation with faithfullness of compliance fill KMS (p-value 0,008<0,05).